Deep Ocean Mining - Scott, S. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2001)
Summary Earth's deep ocean beyond the continentalrises at depths greater than approximately1000 m constitutes about half of thesurface area of the planet and hosts severalmineral resources that have been or aresoon to be investigated for commercialrecovery. These include manganesenodules (copper, nickel, cobalt), manga-nese crusts (cobalt, platinum groupelements), and polymetallic sulphides(copper, zinc, lead, silver, gold, barium).Polymetallic sulphides, formed by hydro-thermal venting on the sea floor, arewidespread in a variety of geologicalsettings, including off Canada's west coast.Some deposits, such as the Atlantis IIDeep in the Red Sea that contains 94million metric tons, rival the size ofanalogous "giant" ore bodies on landalthough most marine deposits are verymuch smaller. Two entrepreneurialcompanies have taken aim at recoveringthese deposits and one, Nautilus Minerals,holds an exploration licence over largeareas offshore of Papua New Guinea. Theenvironmental consequences of miningthe polymetallic sulphides are not well known but there is evidence that oceanmining may actually be less deleterious tothe planet than land mining. Canadiansare in a good position to play a major rolein this new industry.